1995
DOI: 10.1021/ja00118a029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Formation of Free 16-Electron Species Rather than Solvate Complexes in the Ultraviolet Irradiation of CpCo(CO)2 in Liquefied Noble Gas Solvents

Abstract: It is now generally well established that photodissociation of a ligand from many transition metal complexes results in the formation of a solvent-stabilized metal center within picoseconds of ligand loss, even in saturated hydrocarbon solvents.1-6 For example, Rayner and co-workers have determined that, in the gas phase, interaction between the tungsten center and hydrocarbons (RH) in (CO)sW(RH) can be as high as 12 kcal/mol,1 234567 and Yang and co-workers have established an approximately 8 kcal/mol binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 0 publications
5
98
0
Order By: Relevance
“…Another possibility is that this absorption is to a relatively long-lived excited triplet state of VC [18]. Excited triplet states of the coordinatively unsaturated complexes CpCo(CO) [19] and Fe(CO) 4 [20] do not appear to solvate, and the IR spectrum of solvated singlet Fe(CO) 4 has C Á/O stretches that are coincident or near-coincident with those of the unsolvated triplet [20].…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that this absorption is to a relatively long-lived excited triplet state of VC [18]. Excited triplet states of the coordinatively unsaturated complexes CpCo(CO) [19] and Fe(CO) 4 [20] do not appear to solvate, and the IR spectrum of solvated singlet Fe(CO) 4 has C Á/O stretches that are coincident or near-coincident with those of the unsolvated triplet [20].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies have shown that, in dilute solutions of alkanes in rare gas liquids, these rare gas molecules can exchange with alkane molecules to form a C-H-activated final product. Measurements of the exchange rates give a time for bond activation of ∼2 µs at a temperature of 73 K. 7 An interesting question in understanding and eventually making use of these reactions is what effect those ligands which are coordinated to the metal center have on the quantum yield of the reaction. The quantum yield of CpRh(CO) 2 is 1%, while the quantum yield of Cp*Rh-(CO) 2 (Cp ) C 5 H 5 ; Cp* ) C 5 (CH 3 ) 5 ) is only 0.2%.…”
Section: Carbon-hydrogen Bond Activationmentioning
confidence: 99%
“…Ultrafast Visible Spectroscopy. It was shown by Bengali et al and Weiller et al 6,7,18 that the reactive intermediate in the Cp*Rh(CO) 2 system is a monocarbonyl, Cp*Rh(CO). An important issue to be resolved then is the state of the 99% of the molecules which are unreactive.…”
Section: Carbon-hydrogen Bond Activationmentioning
confidence: 99%
“…16,17 For example, though 16-electron CpML (M = Rh, Ir) species readily break unactivated sp 3 CÀH bonds, the related cobalt version is unreactive, likely due to differences in spin state of the intermediate. 16,18 Caulton and co-workers have observed similar inertness of triplet, 16-electron PNPCo I pincer complexes toward alkane CÀH bonds. 19 However, recent development of the catalytic transfer dehydrogenation of silyl-protected amines by Brookhart and coworkers using Cp*Co(η 2 -H 2 CdCH(SiMe 3 )) 2 demonstrates sp 3 CÀH activation can be achieved using Co under certain conditions.…”
mentioning
confidence: 99%